MiR‐19b controls cardiac fibroblast proliferation and migration. Issue 6 (6th April 2016) - Zhong, Chongjun; Wang, Kun; Liu, Ying; Lv, Dongchao; Zheng, Bo; Zhou, Qiulian; Sun, Qi; Chen, Ping; Ding, Shengguang; Xu, Yiming; Huang, Haitao
Abstract: Cardiac fibrosis is a fundamental constituent of a variety of cardiac dysfunction, making it a leading cause of death worldwide. However, no effective treatment for cardiac fibrosis is available. Therefore, novel therapeutics for cardiac fibrosis are highly needed. Recently, miR‐19b has been found to be able to protect hydrogen peroxide (H2 O2 )‐induced apoptosis and improve cell survival in H9C2 cardiomyocytes, while down‐regulation of miR‐19b had opposite effects, indicating that increasing miR‐19b may be a new therapeutic strategy for attenuating cellular apoptosis during myocardial ischaemia–reperfusion injury. However, considering the fact that microRNAs might exert a cell‐specific role, it is highly interesting to determine the role of miR‐19b in cardiac fibroblasts. Here, we found that miR‐19b was able to promote cardiac fibroblast proliferation and migration. However, miR‐19b mimics and inhibitors did not modulate the expression level of collagen I. Pten was identified as a target gene of miR‐19b, which was responsible for the effect of miR‐19b in controlling cardiac fibroblast proliferation and migration. Our data suggest that the role of miR‐19b is cell specific, and systemic miR‐19b targeting in cardiac remodelling might be problematic. Therefore, it is highly needed and also urgent to investigate the role of miR‐19b in cardiac remodelling in vivo .